Synthesis of eight-membered iminocyclitols from D-glucose - Jadhav, Vrushali H.; Bande, Omprakash P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2010)
The Baylis-Hillman reaction of 3-o-benzyl-alpha-d-xylo-pentodialdo-1,4-furanose 2 afforded a diastereomeric mixture of L-ido- and D-gluco-configurated alpha-methylene-beta-hydroxy esters 3a and 3b, respectively, in 1:1 ratio. Conjugate addition of benzyl amine on 3a gave adduct 4a as a major product while, addition of benzyl amine to 3b gave only one diastereomer 4b. Reduction of ester functionality in 4a/4b, opening of 1,2-acetonide functionality followed by reductive amino-cyclization under hydrogenation condition afforded azocanes 1c/1d in good yield. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Baylis-Hillman reaction; Conjugate addition; diastereoselectivity; Iminosugars